IMPLEMENTATION OF COLLABORATIVE GOVERNANCE IN ENVIRONMENTAL SANITATION MANAGEMENT ADIWIYATA POLICY - Rohimatush Shofiyah Shofiyah; Putri Robiatul Adawiyah (POLITICO, 2022)
Collaboration in environmental sanitation management activities was carried out between a team from the University of Muhammadiyah Jember, which was funded by Dikti Litbang PP Muhammadiyah together with ABK boarding school KH. Ahmad Dahlan Banyuwangi in an effort to realize good governance in environmental sanitation management and the implementation of healthy living for the community.Collaborative governance between the public and non-public or private sectors in the administration of government or governance, includes the totality of all institutions and elements of society, both government and non-government. In the concept of governance, several public affairs that were previously managed by a single actor, namely the government, become jointly managed with other actors such as the private sector and the community. the existence of governance makes the government no longer dominant and creates democracy in the administration of government and public affairs. The institutions of governance include three domains, namely the state (state or government), the private sector (private sector or the business world) and society (society) which interact with each other and carry out their respective functions, carry out their respective functions in the implementation of collaborative environmental sanitation management.